Big Five personality traits and sex - Uwe Jirjahn; Martha Ottenbacher (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2020)
Sexual well-being plays an important role in the quality of life. Against this background, we provide an economics-based approach to the relationship between the Big Five personality traits and various dimensions of sexuality. From a theoretical viewpoint, personality influences sexual well-being not only by how a person feels about sex, but also by how the person behaves in a sexual relationship. Personality shapes information sharing about sexual preferences, the way dissonant sexual preferences of the partners are handled, and the extent to which the person is committed to promises made to the partner. Using a large representative dataset from Germany, we find that personality traits play a role in a person's own sexual satisfaction, in (the self-assessment of) fulfilling the partner's sexual needs and desires, in sexual communication, in actual and desired frequency of sex, and in extradyadic affairs.
Keywords: D10; D91; J10; J12; 330; Big Five Personality Traits; Sexual Satisfaction; Frequency of Intercourse; Sexual Infidelity; Sexual Communication; Family Economics